Standardized Total Tract Digestible Phosphorus Requirement of 25- to 50-lb Pigs Fed Diets Containing Phytase - C. M. Vier; S. S. Dritz; M. D. Tokach; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 2,140 barrows and gilts (PIC 337 × Camborough) with an initial pen average body weight (BW) of 24.5 ± 0.53 lb were used in a 21 d growth trial to determine the standardized total tract digestible phosphorus (STTD P) requirement of nursery pigs from 25 to 50 lb fed diets containing 1,000 phytase units (FYT). Pigs were weaned at approximately 19 d of age and allotted to pens according to gender and sow farm of origin. There were 12 replicate pens per treatment and 24 to 27 pigs per pen. Pens of pigs were randomly allotted to experimental diets based on average BW 25 d post-weaning, in a randomized complete block design. The 7 dietary treatments consisted of 0.30, 0.33, 0.38, 0.43, 0.48, 0.53, and 0.58% STTD P, which included the expected release of phytase. These values represented 90, 100, 115, 130, 145, 160 and 175% of the National Research Council (NRC) requirement estimate for STTD P for pigs weighing between 25 to 55 lb, respectively. The diets contained 1,000 FYT of Ronozyme Hiphos 2500 (DSM Nutritional Products, Inc., Parsippany, NJ) with assumed releasing values of 0.15% availablePand 0.132% STTD P. Two corn-soybean meal-based diets were formulated to contain 0.30 and 0.58% STTD P by increasing the inclusion of limestone and monocalcium phosphate at the expense of corn, maintaining a similar 1.17:1 total Ca:P ratio across treatments. These two diets were blended using a robotic feeding system to achieve the intermediate STTD P levels. Increasing STTD P quadratically improved (P<0.05) average daily gain (ADG) and feed efficiency (F/G). The greatest improvement was observed as the STTD P was increased from 0.30 to 0.43% for ADG, and from 0.30 to 0.38% for F/G, with no further improvements thereafter. Final BW and average daily feed intake (ADFI) increased linearly (P<0.05) up to the highest STTD P level. The grams of STTD P intake per day and grams of STTD P intake per kilogram of gain where growth rate reached a point of diminishing returns in response to increased STTD P were greater than the NRC requirement estimates. Income over feed cost improved quadratically (P<0.05), with the highest income being observed at 0.43% STTD P. For both ADG and feed efficiency (modeled as G:F), the broken-line linear (BLL) model demonstrated best fit. The BLL plateau was estimated at 0.40% STTD P for ADG and at 0.37% STTD P for G:F. In conclusion, the estimated STTD P requirement for nursery pigs from 25 to 50 lb fed diets containing 1,000 units of phytase ranged from 0.37 to 0.43% depending on the response criteria. These results indicate that STTD P required to optimize performance and economic return of 25- to 50-lb pigs is greater than the NRC requirement estimate.
Keywords: growth; digestible phosphorus; nursery pigs; phytase